A Comparison of Non-verbal Maternal Care of Male and Female Infants in India and the United Kingdom: The Parent-Infant Caregiving Touch Scale in Two Cultures - Hodsoll, John; Pickles, Andrew; Bozicevic, Laura; Supraja, Thirumalai Ananthanpillai; Hill, Jonathan; Chandra, Prabha S.; Sharp, Helen (Frontiers in Psychology, 2022)
Differences in infant care-giving behavior between cultures have long been noted, although the quantified comparison of touch-based caregiving using uniform standardized methodology has been much more limited. The Parent-Infant Caregiving Touch scale (PICTS) was developed for this purpose and programming effects of early parental tactile stimulation (stroking) on infant hypothalamic pituitary adrenal (HPA) axis functioning (stress-response system), cardiovascular regulation and behavioral outcomes, similar to that reported in animals, have now been demonstrated. In order to inform future studies examining such programming effects in India, we first aimed to describe and examine, using parametric and non-parametric item response methods, the item response frequencies and characteristics of responses on the PICTS, and evidence for cross- cultural differential item functioning (DIF) in the United Kingdom (UK) and India. Second, in the context of a cultural favoring of male children in India, we also aimed to test the association between the sex of the infant and infant “stroking” in both cultural settings. The PICTS was administered at 8-12 weeks postpartum to mothers in two cohort studies: The Wirral Child Health and Development Study, UK (n = 874) and the Bangalore Child Health and Development Study, India (n = 395). Mokken scale analysis, parametric item-response analysis and structural equation modelling for categorical items was used. Items for two dimensions, one for stroking behavior and one for holding behavior, could be identified as meeting many of the criteria required for Mokken scales in the UK, only the stroking scale met these criteria in the sample from India. Thus, while a comparison between the two cultures was possible for the stroking construct, comparisons for the other non-verbal parenting constructs within PICTS was not. Analyses revealed higher rates of early stroking being reported for the UK than India, but no sex-differences in rates in either country and no differential sex difference by culture. We conclude that PICTS items can be used reliably in both countries to conduct further research on the role of early tactile stimulation in shaping important child development outcomes.